2012
DOI: 10.1021/nn3022469
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Emission Quantum Yield of Single Gold Nanorods as a Function of Aspect Ratio

Abstract: We report on the one-photon photoluminescence of gold nanorods with different aspect ratios. We measured photoluminescence and scattering spectra from 82 gold nanorods using single-particle spectroscopy. We found that the emission and scattering spectra closely resemble each other independent of the nanorod aspect ratio. We assign the photoluminescence to the radiative decay of the longitudinal surface plasmon generated after fast interconversion from excited electron-hole pairs that were initially created by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
255
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(293 citation statements)
references
References 47 publications
(82 reference statements)
34
255
0
1
Order By: Relevance
“…The similarity of the optical absorption and light emission spectra of AuNR has been noted before (12,17,19,20) and is typically attributed to light emission associated with the plasmon resonance of the AuNR (19,20). The proposed mechanisms of the luminescence involve (i) the creation of energetic electronhole pairs by the 488-nm photon; (ii) the relaxation of these electron-hole pairs by excitation of the collective longitudinal plasmon; (iii) radiative decay of the longitudinal plasmon by emission of near infrared photons.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The similarity of the optical absorption and light emission spectra of AuNR has been noted before (12,17,19,20) and is typically attributed to light emission associated with the plasmon resonance of the AuNR (19,20). The proposed mechanisms of the luminescence involve (i) the creation of energetic electronhole pairs by the 488-nm photon; (ii) the relaxation of these electron-hole pairs by excitation of the collective longitudinal plasmon; (iii) radiative decay of the longitudinal plasmon by emission of near infrared photons.…”
Section: Resultssupporting
confidence: 76%
“…Because the plasmon resonance is fixed by the geometry of the AuNR, a change in the excitation wavelength will not change the peak position. Further support for this description comes from prior studies (12,17,19,20) which used varying excitation wavelengths and found that the emission peak of AuNRs overlapped with the optical absorption or dark-field scattering peak.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Note that in a lossy medium, e.g. in metals, the bare γ 0 21 will be dominated by nonradiative processes, 81,82 leading to small quantum yields (QY) γ r,0 21 /γ 0 21 ≪ 1. Note also that technically, the calculation of the Purcell factor requires integration over the gain bandwidth,…”
Section: Depend On the Corresponding Macroscopic Gain Profilementioning
confidence: 99%
“…Owing to the strong coupling between the excited electron-hole pairs and the LSPRs, the position and shape of the plasmon-enhanced PL spectra have been demonstrated to be modulated by the LSPRs. 11,14,[21][22][23][24] However, LSPRs supported by those gold nanostructures usually exhibit low quality factors, 7,14,21 and consequently, only the reshaped PL spectra with broad linewidths are observed. In this work, we investigate the PL generated from the gold nanoshells of the dielectric-metal core-shell resonators (DMCSRs).…”
Section: Introductionmentioning
confidence: 99%